30 Years Of On-Stream Analysis At The Pyhasal Mine - S. Uihteenmaki (Society for Mining, Metallurgy & Exploration, 1999)
Pyhasalmi is a massive sulfide orebody located in central Finland. The mine has been in operation since 1962. The flotation concentrator produces Cu, Zn, Pb and pyrite concentrates. The plant has used an on-stream analyzer for process control since 1968. The original analyzer has overlived a few generations of minicomputers, but the analytical parts are essentially unchanged. The on-stream analyzer is a critical component in plant process control system, which has made Pyhasaltni one of the pioneers in the art of computer control and optimization of flotation plants. The paper summarizes the experiences gained from the use of the high performance elemental analyzer system and the proven benefits from the use of on-stream analyzers at a complex sulfide flotation. The aging analyzer is approaching the end of its useful life. A new state of the art analyzer system is undergoing testing at Pyhasalmi.